2022
DOI: 10.3390/life12030400
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Temperature and Osmotic Stress Impact on Seed Germination Rate and Seedling Growth of Eruca sativa Mill. via Hydrothermal Time Model

Abstract: Germination models are quite helpful in predicting emergence times, dormancy periods, and their applications in crop management. This study investigated the germination behaviors of Eruca sativa Mill. in response to fluctuations in temperatures (Ts) and water potentials (ψs). Germination percentage (GP) increased 95% with rising temperature within the range of 20–30 °C, and decreased 25% at 5 °C. Moreover, each ψ and T resulted in a decrease in GP as ψ decreased. Further, we noted that the θT1 value was substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 65 publications
6
25
0
Order By: Relevance
“…Later on, Ts > To, the θH was constant (2.4 MPah −1 in Pirsabak 15 and 0.96 MPah −1 in Shahkar), and only Ψ b(50) was raised with the rising temperature, which resulted in an increase in germination times and a decline in germination rate. Likewise, previous studies on potatoes [17] and watermelon [7] observed an increase in θH numerical quantity at sub-optimal TT. The θH value can be used in a seed lot as a seed quality indicator, as reported previously [35].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Later on, Ts > To, the θH was constant (2.4 MPah −1 in Pirsabak 15 and 0.96 MPah −1 in Shahkar), and only Ψ b(50) was raised with the rising temperature, which resulted in an increase in germination times and a decline in germination rate. Likewise, previous studies on potatoes [17] and watermelon [7] observed an increase in θH numerical quantity at sub-optimal TT. The θH value can be used in a seed lot as a seed quality indicator, as reported previously [35].…”
Section: Discussionsupporting
confidence: 70%
“…The To value (20 • C) was also measured to be closer to that described by [37,38], who reported the To for Triticum aestivum germination ranged from 20-25 • C. The Tc value at 35 • C observed was equal to the Tc value in this study exported by [38] (above 31 • C), [37] (above 30 • C), and [39] (35-42 • C). [28] proposed that using the hydrothermal time models (Equations ( 5) and ( 7)) along with a standardization factor ([1-(Ψ/Ψ b(g))] tg), all tg at constant temperature and solute potential are measured on a thermal time scale, which bears the same finding in watermelon [7] and potato [17]. In the present study, we used this factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations